Вчинення злочину на ґрунті статевої приналежності як обставина, яка обтяжує покарання - Фідря Ю.; Fidria Yu. (Волин. нац. ун-т. ім. Лесі Українки, 2020)
У статті проаналізовано одну з обставин, що обтяжує покарання, яку включено до КК України як наслідок реалізації вимог Стамбульської конвенції, – вчинення злочину на ґрунті статевої приналежності. Наголошено на некоректності формулювання даної обставини у світлі гендерного контексту. Саме лише закріплення такої обставини у КК України (навіть у існуючій редакції) не забезпечує реального захисту прав, гарантованих ст. 24 Конституції України та іншими її нормами. З огляду на викладені міркування, обставина, що обтяжує покарання, передбачена п. 3 ч. 1 ст. 67 КК України, потребує суттєвого доопрацювання. Відповідно, автором запропоновано власну її редакцію.The article analyzes one of the aggravating circumstances included in the Criminal Code of Ukraine as a consequence of the implementation of the requirements of the Istanbul Convention – the commission of a crime based on gender identity. The essence of this circumstance implies a negative or derogatory attitude of the convict to the representatives of another sex or his non-acceptance of the representatives of another sex. The author argues that the wording of this circumstance is incorrect in the light of the gender context of the Istanbul Convention, as sexuality does not cover sexual orientation and gender, and the application of the law on criminal liability by analogy is prohibited. The incompleteness of the terminology and substitution of the concepts in the Criminal code of Ukraine results in low efficiency of the norm and makes the mechanism of its implementation in practice imperfect. First of all, significant difficulties will arise in the course of its detection and proving. The author suggests introducing changes to item 3 of Chapter 67 of the Criminal Code of Ukraine as to formulating the circumstance, which aggravates the punishment: «committing a crime on the basis of racial, national, religious hatred, or dissension, or on the basis of sexual orientation, sex or gender affiliation».
Committing a Crime on the Ground of Gender Identity as an Aggravating Circumstance in Punishment
Keywords: обставини, які обтяжують покарання; статева приналежність; гендер; Стамбульська конвенція; гендерно обумовлене насильство; sex; aggravating circumstances; gender affiliation; Istanbul Convention; gender-based violence